Averrhoa bilimbi Linn.: A review of its ethnomedicinal uses, phytochemistry, and pharmacology - AM, Alhassan; Ahmed, Qamar Uddin (Medknow Publications and Media Pvt. Ltd, 2016)
Averrhoa bilimbi Linn. is principally cultivated for medicinal purposes in many tropical and subtropical countries of the world. Literature survey about this plant shows that A. bilimbi is mainly used as a folk medicine in the treatment of diabetes mellitus, hypertension, and as an antimicrobial agent. The prime objective of this review is to accumulate and organize literature based on traditional claims and correlate those with current findings on the use of A. bilimbi in the management of different ailments. Through interpreting already published scientific manuscripts (1995 through 2015) retrieved from the different scientific search engines, namely Medline, PubMed, EMBASE, and Science Direct databases, published articles and reports covering traditional and scientific literature related to A. bilimbi's potential role against various ailments have been thoroughly evaluated, interpreted, and discussed. Several pharmacological studies have demonstrated the ability of this plant to act as antidiabetic, antihypertensive, thrombolytic, antimicrobial, antioxidant, hepatoprotective, and hypolipidemic agent. A. bilimbi holds great value in the complementary and alternative medicine as evidenced by the substantial amount of research on it. Therefore, we aimed to compile an up-to-date and comprehensive review of A. bilimbi that covers its traditional and folk medicine uses, phytochemistry, and pharmacology. Hence, this paper presents an up-to-date and comprehensive review of the ethnomedicinal uses, different chemical constituents, and pharmacological activities of A. bilimbi. So far, the biologically active agents have not been isolated from this plant and this can be a good scientific study for the future antidiabetic, antihypertensive, and antimicrobial implications. Hence, this review targets at emphasizing the diverse traditional claims and pharmacological activities of A. bilimbi with respect to carrying out more scientific studies to isolate active principles through advanced technology. © 2017 Journal of Pharmacy and Bioallied Sciences | Published by Wolters Kluwer - Medknow.